Identification of ST3AGL4, MFHAS1, CSNK2A2 and CD226 as loci associated with systemic lupus erythematosus (SLE) and evaluation of SLE genetics in drug repositioning. Issue 7 (6th April 2018) - Wang, Yong-Fei; Zhang, Yan; Zhu, Zhengwei; Wang, Ting-You; Morris, David L; Shen, Jiangshan Jane; Zhang, Huoru; Pan, Hai-Feng; Yang, Jing; Yang, Sen; Ye, Dong-Qing; Vyse, Timothy J; et al.
Abstract : Objectives: Systemic lupus erythematosus (SLE) is a prototype autoimmune disease with a strong genetic component in its pathogenesis. Through genome-wide association studies (GWAS), we recently identified 10 novel loci associated with SLE and uncovered a number of suggestive loci requiring further validation. This study aimed to validate those loci in independent cohorts and evaluate the role of SLE genetics in drug repositioning. Methods: We conducted GWAS and replication studies involving 12 280 SLE cases and 18 828 controls, and performed fine-mapping analyses to identify likely causal variants within the newly identified loci. We further scanned drug target databases to evaluate the role of SLE genetics in drug repositioning. Results: We identified three novel loci that surpassed genome-wide significance, including ST3AGL4 (rs13238909, pmeta =4.40E-08), MFHAS1 (rs2428, pmeta =1.17E-08) and CSNK2A2 (rs2731783, pmeta =1.08E-09). We also confirmed the association of CD226 locus with SLE (rs763361, pmeta =2.45E-08). Fine-mapping and functional analyses indicated that the putative causal variants in CSNK2A2 locus reside in an enhancer and are associated with expression of CSNK2A2 in B-lymphocytes, suggesting a potential mechanism of association. In addition, we demonstrated that SLE risk genes were more likely to be interacting proteins with targets of approved SLE drugs (OR=2.41, p=1.50E-03) which supports the role of genetic studies to repurpose drugs approved for other diseases for the treatment of SLE. Conclusion: This study identified three novel loci associated with SLE and demonstrated the role of SLE GWAS findings in drug repositioning.